2014
DOI: 10.1590/s0036-46652014000600008
|View full text |Cite
|
Sign up to set email alerts
|

Serological Markers of Viral, Syphilitic and Toxoplasmic Infection in Children and Teenagers With Nephrotic Syndrome: Case Series From Mato Grosso State, Brazil

Abstract: Some infections can be the cause of secondary nephrotic syndrome. The aim of this study was to describe the experience of a Renal Disease Reference Clinic from Central Brazil, in which serological markers of some infectious agents are systematically screened in children with nephrotic syndrome. Data were obtained from the assessment of medical files of all children under fifteen years of age, who matched nephrotic syndrome criteria. Subjects were tested for IgG and IgM antibodies against T. gondii and cytomega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(30 reference statements)
2
3
0
1
Order By: Relevance
“…In our study there were non-signi icant differences between IgM positive-patients vs IgM-negative patients regarding age, sex and irst attack or relapsed NS patients (p>0.05); this is in agreement with [11], in their study they found. (3 cases relapsed from the 7 nephrotic children cases with cmv IgM + ve ) and 103 (60.9%) out of the 169 nephrotic children were male but disagree regarding to age as they found the median age on the irst visit was 44 months.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study there were non-signi icant differences between IgM positive-patients vs IgM-negative patients regarding age, sex and irst attack or relapsed NS patients (p>0.05); this is in agreement with [11], in their study they found. (3 cases relapsed from the 7 nephrotic children cases with cmv IgM + ve ) and 103 (60.9%) out of the 169 nephrotic children were male but disagree regarding to age as they found the median age on the irst visit was 44 months.…”
Section: Discussionsupporting
confidence: 92%
“…Here, we investigate the link between CMV infect ion and NS in children. In our study we found that 7 (12%) of nephrotic syndrome children cases were CMV IgM +ve, 53 (88%) were CMV IgM -ve and all 60 screened children were CMV IgG +ve (100%), This is in agreement with [11], who investigated Serological markers of viral, syphilitic and toxoplasmic infection in children and teenagers with nephrotic syndrome.…”
Section: Discussionsupporting
confidence: 91%
“…According to Soares et al [9] There was a significant decrease in the incidence and transmission of infection nowadays in Brazil because of the wider vaccination administration to children. This may explain less incidence of this infection as a cause of NS; While Alwadhi et al [5] reported that of the 76 activities, 8 were excluded from analysis.…”
Section: Discussionmentioning
confidence: 99%
“…While not all cases receiving azathioprine presented with active disease .that means that cyclosporine precipitate infection. According to Soares et al [9] immunosuppressant in children with chronic infections may lead to the deterioration of the infection and of the general clinical state. So; most regimes of management of children with NS suggest screening of infections, because these may need specific treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Według brazylijskich badaczy u 4,1% dzieci z zespołem nerczycowym stwierdza się wykładniki świeżej infekcji wirusem cytomegalii (IgM). Autorzy twierdzą, że obecność przeciwciał w klasie IgM u dzieci z objawami niedawno przebytej infekcji układu oddechowego mogą wskazywać na związek CMV z rozwojem zespołu nerczycowego (2) . Według Dossier i wsp.…”
Section: Case Reportunclassified